2015
DOI: 10.5598/imafungus.2015.06.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Cercosporoid fungi (Mycosphaerellaceae) 3. Species on monocots (Poaceae, true grasses)

Abstract: The third part of a series of monographic treatments of cercosporoid fungi (formerly Cercospora s. lat., Mycosphaerellaceae, Ascomycota) continues with a treatment of taxa on monocots (Liliopsida; Equisetopsida, Magnoliidae, Lilianae), covering asexual and holomorph species with mycosphaerella-like sexual morphs on true grasses (Poaceae), which were excluded from the second part. The species concerned are keyed out, alphabetically listed, described, illustrated and supplemented by references to previously publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
1
24
0
5
Order By: Relevance
“…The type species of Cercospora , Cercospora depazeoides (= Cercospora penicillata ) (see Braun 1995 : 41), is a common, widespread cercosporoid fungus on elderberry. Re-examinations of type material and numerous other collections revealed that this species is conspecific with Pseudocercospora sambucigena ( Braun et al. 2015 ), which is a proven species of Pseudocercospora ( Crous et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type species of Cercospora , Cercospora depazeoides (= Cercospora penicillata ) (see Braun 1995 : 41), is a common, widespread cercosporoid fungus on elderberry. Re-examinations of type material and numerous other collections revealed that this species is conspecific with Pseudocercospora sambucigena ( Braun et al. 2015 ), which is a proven species of Pseudocercospora ( Crous et al.…”
Section: Resultsmentioning
confidence: 99%
“…These fungi represent a very large heterogeneous group for which the existing monographs ( Chupp, 1954 , Braun, 1995 , Braun, 1998 , Crous and Braun, 2003 ) are in urgent need of revision (e.g. Braun et al., 2013 , Braun et al., 2014 , Braun et al., 2015 ). With the introduction of phylogenetic analyses based on DNA sequences, the Mycosphaerellaceae has been more narrowly defined with names of asexual genera now being used to identify morphologically distinct monophyletic clades, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Konidia menunjukkan ciri hialin, memiliki sekat dengan (1-)3-5(-12) septa, berbentuk silindris, serta bentuk konidia lurus dan sedikit melengkung di bagian ujungnya. Panjang konidia C.oryzae (10-)15-65 (-85)x3-6,5μm (Braun et. al.…”
Section: Bahan Dan Metodeunclassified
“…2013 ); part two dedicated to species on monocots, excluding true grasses ( Braun et al . 2014 ); and part three with a treatment of cercosporoids on hosts of Poaceae ( Braun et al . 2015 ).…”
Section: Introductionmentioning
confidence: 99%